PELATIHAN KENDALI LAMPU SECARA OTOMATIS UNTUK LAMPU PENERANGAN JALAN DESA SIMPANGAN - Bagas Setia Ajie Sutikno; Muhammad Ilyas Sikki (An-Nizam, 2022)
Energy that plays an important role in everyday life is electricity. The need for electricity is really important, because most daily devices uses electrical energy. However, the rapid development of technology has increased the use of electrical energy. The current demand for electrical energy is close to the production capacity of electrical energy. Excessive use of electrical energy is one of the triggers for the large increase in electrical energy consumption apart from the increase in new loads by development. The effects of excessive energy use also have an impact on an uncertain climate, and can lead to an increase in global temperatures. Controlling the use of electrical energy needs to be done in an effort to save energy. Efforts to save electricity can be started from controlling the use of electricity in street lighting. Control efforts are carried out by holding community training on the application of automatic light control to be applied to public street lighting. The training includes counseling on the importance of saving electrical energy, introduction to lighting automation systems, introduction to supporting components and assembling automatic lamp control devices. That way, people are able to reduce their consumption of electrical energy by implementing an automatic light control system for street lighting.